In Situ-Monitoring of Biofilm Formation by Using Surface-Enhanced Raman Scattering. Issue 5 (May 2013) - Efeoglu, Esen; Culha, Mustafa
A biofilm is a complex biochemical structure composed of microorganisms and extracellular polymeric substances used by microorganisms to adhere to each other and to surfaces. The monitoring of molecular changes during biofilm formation in situ can provide valuable insights in medicine, microbiology, and industrial processes. In this study, we investigated the characterization of biofilm produced by two model bacteria by using surface-enhanced Raman scattering (SERS) with the use of core silver (AgNPs)–shell chitosan nanoparticles (c-AgNPs), which are prepared by coating citrate-reduced AgNPs with a thin layer of chitosan averaging 10 nm. The chitosan thin film acts as porous layer and prevents the excess interactions of biological media secreted by bacteria. The two model bacteria, Escherichia coli and Staphylococcus cohnii, gram positive and gram negative, respectively, were chosen for the study. The SERS spectra were acquired directly from the growth culture by simply placing c-AgNPs substrate on the biofilm formed during the growth of the bacteria for in situ monitoring. It was found that c-AgNPs are effective SERS substrates to monitor molecular changes in the biofilm during the biofilm formation.